Polish contemporary art to the anti-semitism of Poles and its political significance = Polska sztuka współczesna wobec antysemityzmu Polaków i jej polityczne znaczenie. Przyczynek do analizy dyskursu elit symbolicznych - Minkner, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents artistic creativity which worked through the problem of Polish anti-Semitism. Almost all discussed works, performances, films, projects appeared after 2000, when Jan Tomasz Gross published his book "Neighbors", in which he described the massacre in the village of Jedwabne (1941) launching a public debate about the responsibility of Poles in the Holocaust of the Jews. In the text, I showed as art, which is conventionally called ?post-Jedwabne? was part of this debate.
Keywords: the political; art and politics; anti-Semitism; discourse symbolic; polityczność; sztuka a polityka; antysemityzm; dyskurs symboliczny